An Analytic Solution for a Vasicek Interest Rate Convertible Bond Model. (1st February 2010) - Deakin, A. S.; Davison, Matt
Abstract : This paper provides the analytic solution to the partial differential equation for the value of a convertible bond. The equation assumes a Vasicek model for the interest rate and a geometric Brownian motion model for the stock price. The solution is obtained using integral transforms.